2022
DOI: 10.1002/hed.27000
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of skeletal muscle evaluation at the third cervical vertebral level for computed tomography‐defined sarcopenia assessment in patients with head and neck cancer

Abstract: Background: Computed tomography (CT)-defined sarcopenia is a prognostic indicator in head and neck cancer (HNC), with the gold standard for muscle evaluation using cross-sectional area (CSA) at the third lumbar vertebra (L3). We compared methods using CSA at the third cervical vertebra (C3).Methods: Muscle CSA was measured at L3, and CSA at C3 was used to estimate L3 CSA using a prediction model. Agreement and sarcopenia diagnosis were evaluated.Results: Good correlation was found between measured and estimate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 45 publications
0
15
0
Order By: Relevance
“…This study aimed to investigate the use of the vertebral landmark of C3 for muscle mass assessment in this population when L3 is not available in diagnostic CT scans. Although a prediction model has been previously suggested by Swartz et al [ 15 ], our group has shown that equation to not have good agreement with gold standard measures at L3 in our population [ 26 ]. The present study is the first to our knowledge to explore the applicability of C3-CSA in prediction modelling for L3-CSA in a majority overweight or obese population.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…This study aimed to investigate the use of the vertebral landmark of C3 for muscle mass assessment in this population when L3 is not available in diagnostic CT scans. Although a prediction model has been previously suggested by Swartz et al [ 15 ], our group has shown that equation to not have good agreement with gold standard measures at L3 in our population [ 26 ]. The present study is the first to our knowledge to explore the applicability of C3-CSA in prediction modelling for L3-CSA in a majority overweight or obese population.…”
Section: Discussionmentioning
confidence: 67%
“…That model, however, was developed from a relatively small ( n = 52), heterogeneous cohort of patients with HNC and cross-validation was not conducted. As previously mentioned, evaluation of the application of the model on an Australian population of mostly overweight or obese patients found that it had weak agreement with measures taken at L3 to an acceptable clinical level [ 26 ]. A mean percentage difference in SMI measures of 5.6% was found (range − 34 to 33.1%, r = 0.548, p < 0.001), which translated clinically to a 5% misclassification of sarcopenia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This prediction rule was used in the present study. A recent study by Vangelov et al questioned the use of C3MA as an evaluation tool of skeletal muscle mass in HNSCC patients [ 38 ]. Although the authors found a good correlation of measured L3MA and calculated L3MA from C3MA, systemic biases were reported with underestimation of L3MA for low values of C3MA and overestimation for high C3MA values and therefore hampering classification of individual patients into sarcopenic and non-sarcopenic.…”
Section: Discussionmentioning
confidence: 99%
“…Skeletal muscle mass (SMM) was defined as the total cross-sectional skeletal muscle area (TMA in cm 2 ). SMI was calculated by dividing the total cross-sectional skeletal muscle area (TMA-cm 2 ) at the level of lumbar vertebra L3 by height squared (m 2 ), which could proportionally reflect whole-body muscles of patients ( 32 , 33 ). And measurements of muscle on sectional CT is considered as the gold standard method at present ( 34 , 35 ).…”
Section: Methodsmentioning
confidence: 99%